Unilateral mandibular coronoid osteoma-An unusual cause for pseudoankylosis - Karthikeya Patil; C J Sanjay; M Meghana; S Viveka (Wolters Kluwer Medknow Publications, 2021)
An osteoma is a benign osteogenic tumor characterized by compact or cancellous bone proliferation with unknown etiology, but it may arise from cartilage or embryonal periosteum. Osteomas are rare, slow growing, usually asymptomatic until their size and position interferes with functioning. This is a report of a 53-year-old male patient who complained of difficulty in opening his mouth, which was diagnosed as an osteoma of mandibular coronoid producing pseudo ankylosis, a very unusual condition. Surgical excision of the tumor was performed, followed by physiotherapy and no recurrence was observed. This case report highlights the rare causes of pseudo ankylosis with significance to early diagnosis and intervention which can prevent further complications to the patient.